Pengaruh Kebiasaan Belajar,Kreativas Belajar, Perhatian Orang Tua, Fasilitas Belajar, Dan Teman Sebaya Terhadap Prestasi Belajar Siswa Kelas X Fase E Pada Mata Pelajaran Ekonomi Di SMAN 1 Bukit Sundi Kabupaten Solok - Yolanda Ifana Putri; Jimmi Ronald; Mona Amelia (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
This research aims to analyze the influence of activity, discipline, family environment, learning This research aims to analyze 1) the partial influence of study habits on student learning achievement, 2) the partial influence of learning creativity on student learning achievement, 3) the partial influence of parental attention on student learning achievement, 4) the partial influence of learning facilities on student learning achievement, 5) the partial influence of peers on student learning achievement, 6) the influence of study habits, learning creativity, parental attention, learning facilities, and peers simultaneously on the learning achievement of class X Phase E students in economics subjects in Bukit Sundi 1 Public High School, Solok Regency. This type of research is associative research. The population in this study were students of class Sampling used a stratified random sampling technique. The instrument used for research was a closed questionnaire using the Multiple Linear Regression test and hypothesis testing using the t test and F test. The research results show that: First, the study habit variable has a positive and significant effect on study achievement. This can be seen from the regression coefficient of 0.131 with t count 2.854 > t table 1.982 while the significant value is 0.005> α0.05. The two learning creativity variables have a positive and significant effect on student learning achievement. This can be seen from the regression coefficient of 0.139 with t count 2.769 > t table 1.982. while the significant value is 0.007<α0.05. The three variables of parental attention have a positive and significant effect on student learning achievement. This can be seen from the regression coefficient of 0.110 with t count 2.295 > t table 1.982. while the significant value is 0.024>α 0.05. The four learning facility variables have a positive and significant effect on student learning achievement. This can be seen from the regression coefficient of 0.186 with t count 2.144 > t table 1.982. while the significant value is 0.034>α 0.05. The five peer variables have a positive and significant effect on student learning achievement. This can be seen from the regression coefficient of 0.166 with a t value of 2.742 > t table 1.982 while the significant value is 0.007 > α 0.05. (6) The variables of learning style, self-confidence, peers, learning discipline and learning facilities together have a positive and significant effect on student learning achievement. The t value is 43.818 > t table 2.30 and the significant value is 0.001 <0.05, p. This means H0 is rejected and Ha is accepted.